Respuesta :
Answer:
y=-4x+13
Step-by-step explanation:
y=mx+b
slope =
1--3/3-4
4/-1
-4/1
y-1=-4(x-3)
y-1=-4x+12
y=-4x+13
Answer:
[tex]y = -4x + 13[/tex]
Step-by-step explanation:
First, find the slope (denoted by the variable, m). Use the following equation:
slope [tex](m) = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
Let:
[tex](x_1, y_1) = (4 , -3)\\(x_2, y_2) = (3 , 1)[/tex]
Plug in the corresponding numbers to the corresponding variables:
[tex]m = \frac{y_2 - y_1}{x_2 - x_1} = \frac{1 - (-3)}{3 - 4} = \frac{1 + 3}{-1} = \frac{4}{-1} = -4[/tex]
Use the slope-intercept form. The slope-intercept form is:
[tex]y = mx + b[/tex]
Use one of the given points to plug in for (x ,y). Also note that the slope (m) is equal to -4. Plug in the corresponding numbers to the corresponding variables:
[tex]y = mx + b\\(x , y) = (3 , 1)\\m = -4\\\\\\1 = (-4 * 3) + b\\1 = (-12) + b\\1 (+12) = b - 12 (+12)\\b = 1 + 12\\b = 13[/tex]
Plug in the slope (m) and the y-intercept (b) to get your equation:
[tex]y = -4x + 13[/tex]
~